Consumer Satisfaction at Babi Guling Pande Egi Restaurant in Beng Village, Gianyar - Arcana, I Nyoman; Massenga, Lidjah Magdalen; Suastuti, Ni Luh; Pranadewi, Putu Mira Astuti; Budiani, Ni Putu Ariesta (Institut Pariwisata dan Bisnis Internasional, 2025)
Balinese suckling pig restaurant is a specialty restaurant that is growing rapidly in Bali. Generally, a restaurant is located in a strategic location or the center of the crowd, but “Babi Guling Pande Egi” restaurant is located in a less strategic location, with an average number of visitors of more than 400 consumers every day. This study aims to determine the factors that affect consumer satisfaction at this restaurant, using multiple regression analysis with 112 respondents. This study concluded that all of the variables had a significant effect on the overall satisfaction of consumers. The largest contribution was achieved by the dimension of brand image, followed by location, price, atmosphere & convenience, service quality, product quality, and lastly is cleanliness & hygiene. This research suggests that restaurant managers open new outlets in other cities in Bali, especially in tourism areas or in the city of Denpasar